Avaliação da suplementação materna com megadose de vitamina A sobre os níveis de retinol e alfa-tocoferol no colostro - Garcia, Lígia Rejane Siqueira (2009)
The vitamins A and E are recognizably important in the initial stages of life and the newborn depends on nutritional adequacy of breast milk to meet their needs. These vitamins share routes of transport to the tissues and antagonistic effects have been observed in animals after supplementation with vitamin A. This study aimed to verify the effect of maternal supplementation with vitamin A megadose (200,000 UI) in the immediate post-partum on the concentration of alpha-tocopherol in colostrum. Healthy parturient women attended at a public maternity natalensis were recruited for the study and divided into two groups: control (n = 37) and supplemented (n = 36). Blood samples of colostrum and milk were collected until 12 hours after delivery. The women of the supplemented group was administered a retynil palmitate capsule and 24 hours after the first collection was obtained the 2nd sample of colostrum in two groups for analysis of retinol and alpha-tocopherol in milk. The mean retinol concentration of 50,7 ± 14,4 μg/dL (Mean ± standard deviation) and alpha-tocopherol of 1217.4 ± 959 mg/dL in the serum indicate the nutritional status biochemical appropriate. Supplementation with retynil palmitate resulted in increase not only retinol levels in the colostrum of the supplemented group (p = 0.002), but also the concentration of alpha-tocopherol (p = 0.04), changing from 1456.6 ± 1095.8 mg/dL to 1804.3 ± 1432.0 mg/dL (milk 0 and 24 respectively) compared to values in the control group, 984.6 ± 750.0 mg/dL and 1175.0 ± 730.8 mg/dL. The women had different responses to supplementation, influenced by baseline levels of retinol in colostrum. Those with previous by low levels of retinol in colostrum (<60 mg/dL) had increased the concentration of alpha-tocopherol in milk, whereas those with adequate levels (> 60 mg/dL), showed a reduction after supplementation. Supplementation with retinol palmitate is an important intervention in situations of high risk for vitamin A deficiency, when considering the need to maternal supplementation, since the excess vitamin can offer unfavorable interactions between nutrients essential for the mother-child group